Prognostic score based on physical frailty in patients with heart failure: a multicenter prospective cohort study (FLAGSHIP). Issue 6 (30th September 2021) - Yamada, Sumio; Adachi, Takuji; Izawa, Hideo; Murohara, Toyoaki; Kondo, Takaaki; ,
Abstract: Background: In patients with heart failure (HF), physical frailty should be assessed to enable risk stratification. No conventional frailty criteria have so far been developed considering HF‐specific outcomes. This study aimed to propose a frailty‐based prognostic score using a nationwide cohort study of Japanese patients with HF. Methods: We analysed 2721 patients hospitalized for HF and capable of walking at discharge (median age: 76 years [interquartile range 67–83], men: 60.5%). Physical frailty was evaluated at discharge using four quantitative measures: usual walking speed, grip strength, Performance Measure for Activities of Daily Living‐8 (PMADL‐8), and Self‐Efficacy for Walking‐7 (SEW‐7). The primary outcome was a composite of HF rehospitalization and all‐cause mortality within 2 years. A cut‐off point was identified for each measure using receiver operating characteristic analysis in a derivation cohort ( n = 1778). Cox proportional hazards model was used to assign a score to each frailty domain according to the correlation with the endpoint. Patients were divided into four categories according to the sum score, and survival was compared by analysing the Kaplan–Meier curve and Cox proportional hazards model. Cumulative incidences of the events according to frailty categories were compared between the derivation cohort and a validation cohort ( n = 943). Results: The cut‐off value and assigned score of each indicator was determined as follows: usual walking speed < 0.98 m/s = 4 points; grip strength < 30.0 kg (men) or 17.5 kg (women) = 5 points; PMADL‐8 ≥ 21 points = 2 points; SEW‐7 ≤ 20 points = 3 points. We stratified patients into four categories according to the sum score: Category I, ≤3 points; Categories II, 4–8 points; Category III, 9–13 points; and Category IV, 14 points. The prevalence and cumulative incidence of the composite outcome for Categories I to IV in the derivation cohort were 27.4%, 25.2%, 26.4%, and 21.0%, and 9.5, 16.3, 26.3, and 36.8/100 person‐years, respectively. Similar results were confirmed in the validation cohort. In Cox proportional hazards model, frailty categories were associated with the composite outcome independent of potential confounders (hazard ratio [95% confidence interval] in reference to Category I: Categories II, 1.51 [0.84–2.72], P = 0.169; Category III, 2.37 [1.32–4.23], P = 0.004; Category IV, 2.66 [1.45–4.89], P = 0.002). Conclusions: The frailty‐based prognostic score proposed in this study was well associated with prognosis and will serve for risk stratification in patients with HF.